Effects of microwave irradiation on the expression of key flavonoid biosynthetic enzyme genes and the accumulation of flavonoid products in Fagopyrum tataricum sprouts. (September 2021) - Ma, Hui; Xu, Xianmeng; Wang, Shunmin; Wang, Junzhen; Peng, Wenping
Abstract: Tartary buckwheat ( Fagopyrum tataricum ) sprouts are an excellent source of dietary flavonoids. Here, we examined the effects of exposing F. tataricum 'Chuanqiao No.1' sprouts to various time/power settings during microwave irradiation, by determining their impact on the expression of key flavonoid biosynthetic enzyme genes and the accumulation of flavonoid products within these plants. Microwave irradiation (300 W/25–75 s) significantly upregulated the transcription of various flavonoid biosynthetic enzyme genes, including FtPAL, FtCHI, and FtFLS2, in Tartary buckwheat sprouts during incubation. Maximum rutin content (25064.19 mg/kg dry weight (DW)) was observed in 5-day-old sprouts after they were treated with microwave irradiation at 300 W/75 s, while maximum chlorogenic acid (497.95 mg/kg DW) and vitexin (345.75 mg/kg DW) content were observed after irradiation at 300 W/50 s. Additionally, maximum quercetin content (342.98 mg/kg DW) was reached in 3-day-old sprouts after irradiation at 300 W/50 s. Significant increases in myricetin and dihydromyricetin content were also observed with extended exposure time (300 W/25–125 s); however, this was countermanded by increasing the power value from 300 W to 500 W. These results suggest that among other treatment conditions, microwaving Tartary buckwheat sprouts at 300 W/50–75 s displays the best results in increasing the flavonoid content in these samples. Graphical abstract: Image 1 Highlights: Sprout length and fresh weight of microwaving Fagopyrum tataricum sprouts are greatly affected. Microwave treatment could induce the upregulation of FtPAL, FtCHI, and FtFLS2 transcription. Microwave treatment could induce the flavonoids accumulation, such as rutin and quercetin. Microwaving sprouts at 300 W/50–75 s displays the best results in flavonoids accumulation.